Assessing the Human Health Benefits of Climate Mitigation, Pollution Prevention, and Biodiversity Preservation - Philip J. Landrigan; Michael Britt; Samantha Fisher; Amelia Holmes; Manasi Kumar; Jenna Mu; Isabella Rizzo; Anna Sather; Aroub Yousuf; Pushpam Kumar (Annals of Global Health, 2024)
Background: Since the Industrial Revolution, humanity has amassed great wealth and achieved unprecedented material prosperity. These advances have come, however, at great cost to the planet. They are guided by an economic model that focuses almost exclusively on short-term gain, while ignoring natural capital and human capital. They have relied on the combustion of vast quantities of fossil fuels, massive consumption of the earth’s resources, and production and environmental release of enormous quantities of chemicals, pesticides, fertilizers, and plastics. They have caused climate change, pollution, and biodiversity loss, the “Triple Planetary Crisis”. They are responsible for more than 9 million premature deaths per year and for widespread disease – impacts that fall disproportionately upon the poor and the vulnerable. Goals: To map the human health impacts of climate change, pollution, and biodiversity loss. To outline a framework for assessing the health benefits of interventions against these threats. Findings: Actions taken by national governments and international agencies to mitigate climate change, pollution, and biodiversity loss can improve health, prevent disease, save lives, and enhance human well-being. Yet assessment of health benefits is largely absent from evaluations of environmental remediation programs. This represents a lost opportunity to quantify the full benefits of environmental remediation and to educate policy makers and the public. Recommendations: We recommend that national governments and international agencies implementing interventions against climate change, pollution, and biodiversity loss develop metrics and strategies for quantifying the health benefits of these interventions. We recommend that they deploy these tools in parallel with assessments of ecologic and economic benefits. Health metrics developed by the Global Burden of Disease (GBD) study may provide a useful starting point. Incorporation of health metrics into assessments of environmental restoration will require building transdisciplinary collaborations. Environmental scientists and engineers will need to work with health scientists to establish evaluation systems that link environmental and economic data with health data. Such systems will assist international agencies as well as national and local governments in prioritizing environmental interventions.